"Backpack Refugee Rights Advocating" in Greece – Access to Justice through Legal Empowerment - Manhart, Magnus (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2020)
The moment asylum seekers arrive in Greece, they are often denied access to justice on different levels. At the same time international volunteer field advocates or Backpack Refugee Rights Advocates have the goal of assisting asylum seekers to master the difficulties of the complex European asylum process. More importantly they can play an important role in the process of legally empowering asylum seekers. This paper will first analyze the different forms of access to justice that are denied to asylum seekers in Greece. Then then paper will proceed with the concept of legal empowerment of asylum seekers and it is argued that the main purpose of Backpack Refugee Rights Lawyers should be enabling asylum seekers and refugees to know and enforce their own rights. At the same time the paper identifies and addresses several problems of the work of Backpack Refugee Rights Lawyers. Overall, it is hoped that this paper will provide field advocates with information about how they can play an integral part in the legal empowerment of asylum seekers and refugees if they act according to certain guidelines.